Juridical Analysis of the Application of Restorative Justice to Alleged Children as Perpetrators of Criminal Acts of Persecution (Study at The Binjai Police) - Nabila Ismira; Syahranuddin (Cattleya Darmaya Fortuna, 2026)
The implementation of restorative justice in cases involving children suspected of committing assault offenses has become an important approach within Indonesia's juvenile criminal justice system, emphasizing child protection, victim recovery, and the best interests of the child. However, the practical application of restorative justice at the investigation stage continues to present legal and procedural challenges, particularly concerning investigators' discretion in determining case eligibility. This study aims to analyze the juridical considerations underlying investigators' decisions, examine the implementation of restorative justice, and identify the obstacles and efforts associated with its application at the Binjai Police. This research employs an empirical legal method using a juridical-empirical approach with descriptive-analytical analysis. Primary data were obtained through interviews with relevant informants, while secondary data were collected through the study of legislation, legal literature, and related scientific publications. The findings indicate that the implementation of restorative justice is guided primarily by Law Number 11 of 2012 concerning the Juvenile Criminal Justice System and the Regulation of the Indonesian National Police Number 8 of 2021 concerning the Handling of Criminal Acts Based on Restorative Justice. Investigators consider various legal and practical factors, including the nature of the offense, the child's age, the consequences of the offense, the willingness of both parties to reconcile, and the restoration of victims' rights. The study also identifies several implementation challenges, including victims' refusal to reconcile, disputes regarding compensation, and limited cooperation from the parties involved. The study concludes that restorative justice provides an effective mechanism for resolving juvenile assault cases when implemented selectively, voluntarily, and consistently with the principles of child protection, legal certainty, and victim-oriented justice.